High performance dielectric elastomers by partially reduced graphene oxide and disruption of hydrogen bonding of polyurethanes. (15th January 2015) - Liu, Suting; Tian, Ming; Yan, Bingyue; Yao, Yang; Zhang, Liqun; Nishi, Toshio; Ning, Nanying
Abstract: Thermally reduced graphene oxide (TRG)/thermoplastic polyurethanes (TPU) dielectric elastomer with high dielectric constant ( k ), low dielectric loss and greatly improved actuated strain at low electric field was prepared by solution blending followed by in situ thermal reduction. The results showed that a good dispersion and alignment of TRG in the TPU matrix was obtained. The k at 10 3  Hz was sharply increased from 7 for pure TPU to 1875 for the composite with 2 vol. % of TRG because of the partial restoration of graphite structure and the great increase in dipole polarizability of TPU caused by the disruption of hydrogen bonds of TPU chains. The dielectric loss at 10 3  Hz of the composite with 2 vol. % of TRG remained low (0.43). Despite of the increase in elastic modulus with the increase in the content of TRG, the great increase in k lead to the great increase in electromechanical sensitivity ( β ). As a result, a 106 times increase in β at 10 3  Hz and 17 times increase in actuated strain at low electric field (250 V/mm) were achieved by adding 2.0 vol% of TRG. This study provides a simple and effective method for the improvement of actuated strain at low electric fields through partial reduction of graphene oxide and the disruption of hydrogen bonds in TPU, facilitating the applications of dielectric elastomers in the biological and medical fields, where a low electric field is required. Graphical abstract: Highlights: We obtained a good dispersion and alignment of GONS in the TPU matrix. We improved the dielectric constant by reducing GONS and disrupting hydrogen bonds. We prepared dielectric elastomer with improved actuated strain at low voltage.